Studies on the Palaeolithic of Western Eurasia : proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France). - Lengyel, György, 1975-; Wilczyński, Jarosław; Sánchez de la Torre, Marta; Mangado, Xavier; Fullola Pericot, Josep Ma. (UISPP proceedings series, 2021)
Papers from Session 4 disseminate a wealth of archaeological data from Bavaria to the Russian Plain, and discuss Aurignacian, Gravettian, Epigravettian, and Magdalenian perspectives on lithic tool kits and animal remains. Session 6 was concerned with lithic raw material procurement in the Caucasus and in three areas of the Iberian peninsula.